Cold Agglutinin Disease: Pathophysiology, Clinical Management, and Emerging Therapeutic Approaches Including Plant-Derived Compounds - Kumar BS, Ashok; NS, Disha; Narayan BA, Dhruthi; R, Kalyani (Journal of Neonatal Surgery, 2025)
Cold Agglutinin Disease (CAD) is a rare form of autoimmune haemolytic anaemia characterized by the binding of cold-reactive antibodies (cold agglutinins) to red blood cells at low temperatures, leading to clumping and haemolysis. Predominantly affecting older adults, CAD can be either primary (idiopathic) or secondary to underlying conditions such as infections, malignancies, or autoimmune disorders. The disease mechanism involves IgM antibodies binding to red blood cells in cold environments, activating the classical complement pathway, and causing haemolysis. Patients typically present with anaemia symptoms, including fatigue and jaundice, as well as cold-induced circulatory issues like acrocyanosis. Diagnosis is confirmed through clinical evaluation, positive direct antiglobulin test, and elevated cold agglutinin titers. Treatment strategies include avoiding cold exposure, supportive care, and pharmacologic interventions such as corticosteroids, rituximab, and emerging complement inhibitors like eculizumab. Recent advances in understanding CAD's molecular mechanisms have led to more targeted therapies. While plant-derived chemicals like curcumin and resveratrol are not yet established treatments, they are under investigation for their potential benefits in autoimmune and haematological disorders, potentially providing future therapeutic options for CAD. This review offers a comprehensive overview of CAD's causes and treatments, emphasizing recent research and future directions.